State Responsibility in Protecting Indonesian Migrant Workers as Fulfillment of Human Rights - Sundary, Rini Irianti; Muslikhah, Umi (Jurnal Ius Constituendum, 2024)
This research aims to examine the state's responsibility in protecting Indonesian migrant workers in an effort to fulfill human rights. Indonesian migrant workers have an important role in the nation's economic development. As a contributor to the country's foreign exchange, legal protection for Indonesian migrant workers abroad is very important. The placement of migrant workers abroad has increased. The increasing interest of Indonesian migrant workers abroad is in line with the growing complexity of problems faced by Indonesian migrant workers in the form of human rights violations, verbal, physical, and sexual harassment, and other violence. The urgency of this research is to determine the role and responsibility of the state in protecting Indonesian migrant workers, especially those abroad, based on existing laws and regulations, such as the existence of Law Number 18 of 2017. This research is normative legal research. Updates and research results carried out by the government regarding the protection of Indonesian migrant workers have been regulated in Law Number 18 of 2017. Forms of protection are carried out starting before placement, during placement, and after placement. From the research conducted, it was concluded that the state's responsibility and protection for Indonesian migrant workers still need to be improved.